Chronic Overlapping Pain Conditions in people with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS): a sample from the Multi-site Clinical Assessment of ME/CFS (MCAM) study - Elizabeth A. Fall; Yang Chen; Jin-Mann S. Lin; Anindita Issa; Dana J. Brimmer; Lucinda Bateman; Charles W. Lapp; Richard N. Podell; Benjamin H. Natelson; Andreas M. Kogelnik; Nancy G. Klimas; Daniel L. Peterson; et al. (BMC Neurology)
Abstract Background Chronic overlapping pain conditions (COPCs), pain-related conditions that frequently occur together, may occur in patients with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) and could impact illness severity. This study aimed to identify comorbid COPCs in patients with ME/CFS and evaluate their impact on illness severity. Methods We used data from 923 participants in the Multi-Site Clinical Assessment of ME/CFS study, conducted in seven U.S. specialty clinics between 2012 and 2020, who completed the baseline assessment (595 ME/CFS and 328 healthy controls (HC)). COPCs included chronic low back pain (cLBP), chronic migraine/headache (cMHA), fibromyalgia (FM), interstitial cystitis/irritable bladder (IC/IB), irritable bowel syndrome (IBS), temporomandibular disorder (TMD). Illness severity was assessed through questionnaires measuring symptoms and functioning. Multivariate analysis of variance and analysis of covariance models were used for analyses. Log-binomial regression analyses were used to compute prevalence of COPCs and prevalence ratios (PR) between groups with 95% confidence intervals. Both unadjusted and adjusted results with age and sex are presented. Results 76% of participants with ME/CFS had at least one COPCs compared to 17.4% of HC. Among ME/CFS participants, cMHA was most prevalent (48.1%), followed by FM (45.0%), cLBP (33.1%), and IBS (31.6%). All individual COPCs, except TMD, were significantly more frequent in females than males. The unadjusted PR (ME/CFS compared to HC) was highest for FM [147.74 (95% confidence interval (CI) = 20.83-1047.75], followed by cLBP [39.45 (12.73-122.27)], and IC/IB [13.78 (1.88-101.24)]. The significance and order did not change after age and sex adjustment. The COPC comorbidities of cLBP and FM each had a significant impact on most health measures, particularly in pain attributes (Cohen’s d effect size 0.8 or larger). While the impact of COPC comorbidities on non-pain attributes and quality of life measures was less pronounced than that on pain, statistically significant differences between ME/CFS participants with and without COPCs were still evident. Conclusions More than 75% of ME/CFS participants had one or more COPCs. Multiple COPCs further exacerbated illness severity, especially among females with ME/CFS. Assessment and management of COPCs may help improve the health and quality of life for patients with ME/CFS.